2001
DOI: 10.1088/0953-4075/34/17/316
|View full text |Cite
|
Sign up to set email alerts
|

K x-ray relative transition probabilities for 39⩽Z⩽68

Abstract: In this paper we report the measurements of the K x-ray relative transition probabilities as follows: Kβ/Kα for the atomic numbers Z = 39, 51, 62, 63, 64, 66, 67 and 68; and Kα2/kα1, kβ11/kα1, kβ21/kβ11 and kβ3/kβ2 for the atomic numbers Z = 62, 63, 64, 66, 67 and 68 as induced by protons at an energy of 3 MeV. The experimental results obtained are then compared with relativistic Hartree-Fock calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…de Pinho, 1971 calculated the relative radiative decay rates of vacancies in the K shell. Moreover, Ximeng et al (2001) reported the measurements of the K X-ray relative transition probabilities in the atomic range 39rZr68 by protons at an energy of 3 MeV. The K relative intensities were measured by McCrary et al (1971) for elements ranging from Ca to Pu.…”
Section: Introductionmentioning
confidence: 99%
“…de Pinho, 1971 calculated the relative radiative decay rates of vacancies in the K shell. Moreover, Ximeng et al (2001) reported the measurements of the K X-ray relative transition probabilities in the atomic range 39rZr68 by protons at an energy of 3 MeV. The K relative intensities were measured by McCrary et al (1971) for elements ranging from Ca to Pu.…”
Section: Introductionmentioning
confidence: 99%